2016
DOI: 10.1007/s11427-016-5007-8
|View full text |Cite
|
Sign up to set email alerts
|

Roles and mechanisms of ginsenoside in cardiovascular diseases: progress and perspectives

Abstract: Ginseng is among the oldest traditional Chinese medicinal herbs and is widely used in China and Southeast Asia. Over the past 50 years, considerable research has focused on the chemical constituents, pharmacological action, and clinical applications of ginseng. In this review, we examine the current state of research on ginseng, including the main active ingredient ginsenoside, its pharmacological effects on the cardiovascular system, and mechanisms of action. We focus on what is known of the effects of ginsen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 21 publications
1
44
1
Order By: Relevance
“…The contained ginsenosides may bestow on ginseng various pharmacological actions [ 14 ]. The ginsenosides Rb and Rg1 produce cardioprotective effects [ 15 ]. Ginsenoside Rh2, the active ingredient extracted from red ginseng and with the molecular formula C 36 H 62 O 8 , has been demonstrated to improve ischemic brain injury in rats [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The contained ginsenosides may bestow on ginseng various pharmacological actions [ 14 ]. The ginsenosides Rb and Rg1 produce cardioprotective effects [ 15 ]. Ginsenoside Rh2, the active ingredient extracted from red ginseng and with the molecular formula C 36 H 62 O 8 , has been demonstrated to improve ischemic brain injury in rats [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…51 The antiplatelet aggregation activity of ginsenoside Rg 1 and Rb 1 has been reported. 52 In addition, they have activities in treating cardiovascular diseases 53 and ischemic stroke, 54 and have anti-inammatory 55 and neuroprotective effects against cerebral ischemia. 56 Rutin had anti-oxidant, 57 anti-carcinogenic, 58 liver protection, 59 anti-inammatory, 60 neuroprotective, 61 and vasoprotective properties.…”
Section: Discussionmentioning
confidence: 99%
“…As an active ingredient of ginseng fruit, GFS plays a crucial role in the treatment of CHD through multiple metabolic pathways including inhibition of platelet aggregation. [171819] The study of Hao et al . [20] showed that Rb1 as an important ingredient of GFS can increase the neural 5-HT concentration and decrease immobility time in the forced swimming test (FST).…”
Section: Introductionmentioning
confidence: 99%